Design of wideband omnidirectional dual-reflector antennas in millimeter waves - Penchel, Rafael A. [UNESP]; Zang, Sandro R.; Bergmann, Jose R.; Moreira, Fernando J. S. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The work investigates the electromagnetic performance of omnidirectional dual-reflector antennas designed to operate with a frequency bandwidth larger than 45% (25-40 GHz). We consider two antenna configurations, distinguished from each other by two different optical ray mappings. A conventional coaxial horn is designed to ensure vertical polarization and stable primary radiation pattern along the operating bandwidth. By employing a geometrical optics synthesis technique, the omnidirectional reflectors are shaped to maximize the directivity of the broadside secondary radiation patterns. For the synthesis, we employ different aperture power distributions and investigate their effect on the antenna gain and return loss when operating over the 40% frequency bandwidth. To access the antenna performance, a full-wave electromagnetic analysis based on the combination of mode matching and method of moments is employed.
Keywords: Omnidirectional antennas; reflector antennas; ultra-wideband antennas